Estrategias de evaluación de los aprendizajes centradas en el proceso - Alsina, M. Inmaculada Bordas; Rodríguez, Flor Á. Cabrera (Revista Española de Pedagogía, 2025)
Our intention in these pages is offering a review of the new leaming assessment perspectives, and assessment techniques used in the classroom. These assessment techniques prove to be not only assessment strategies but can also be considered evaluation curriculum contents. Basing on this, we first analyze those factors, which have a major impact on the new ways of thinking and caring about assessment. We present an outline of the evolution of the meaning and conceptualization of assessment in contrast with the traditional perspectives. ln the last part of the article, we present various assessment strategies wlùch attend to provide a response to the new concepts of assessment: portfolio, conceptual maps and the retlective diary.